2002
DOI: 10.1002/sia.1342
|View full text |Cite
|
Sign up to set email alerts
|

Angle‐resolved core‐level spectroscopy of Zr1Nb alloy oxidation by oxygen, water and hydrogen peroxide

Abstract: The initial oxidation of Zr1Nb alloy in oxygen, water and hydrogen peroxide at room temperature has been studied by angle-resolved x-ray photoelectron spectroscopy (ARXPS). The clean surface of alloy has been prepared either by scraping under ultrahigh (10 −10 mbar) vacuum or by argon ion sputtering.The four well-defined oxidation states of Zr were identified in the oxide films on Zr1Nb. The results of the ARXPS study were consistent with a layered structure of the oxide film, with zirconium dioxide in the out… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(13 citation statements)
references
References 17 publications
1
12
0
Order By: Relevance
“…Aer deconvolution calculation of the Zr3d spectrum in the ZrO 2 catalyst, Zr3d can also be decomposed into 2 groups of peaks: Zr (4Àx)+ ($181.7 eV), ZrO 2 ($182.2 eV). 42,43 In Table 4, by calculating the ratio of the area of the Zr (4Àx)+ peak to the total area of the Zr (4Àx)+ and ZrO 2 peaks, the concentration ratio of Zr (4Àx)+ can be quantitatively estimated.…”
Section: Xps Analysis Of Catalystmentioning
confidence: 99%
“…Aer deconvolution calculation of the Zr3d spectrum in the ZrO 2 catalyst, Zr3d can also be decomposed into 2 groups of peaks: Zr (4Àx)+ ($181.7 eV), ZrO 2 ($182.2 eV). 42,43 In Table 4, by calculating the ratio of the area of the Zr (4Àx)+ peak to the total area of the Zr (4Àx)+ and ZrO 2 peaks, the concentration ratio of Zr (4Àx)+ can be quantitatively estimated.…”
Section: Xps Analysis Of Catalystmentioning
confidence: 99%
“…From Figure 3(A), doublet peaks around at 181.5 and 183.9 eV were attributed to the Zr3d5/2 and Zr3d3/2, respectively, which arose from the doping Zr 4+ ions by substituting lattice titanium in doped TiO 2 sample, because the Zr3d5/2 peak falls between that for ZrO 2 (183.5 eV) 19 and metallic Zr (179 eV). 20 As seen from Figure 3(B), a single N peak at binding energy of 399.5 eV was observed, which was attributed to the presence of substitutional N in N Ti O bond, indicating that some lattice oxygen atoms were substituted by nitrogen.…”
Section: Xps Analysismentioning
confidence: 96%
“…Analogously, the oxide films on Zr usually present a layered structure determined by the stoichiometry of different oxides that grow from the metallic substrate toward the outer surface in a sequence of increasing oxidation numbers, namely Zr2O/ZrO/Zr2O3/ZrO2 [1,58]:…”
Section: Comments On the Corrosion Resistance Of Passive Layers Formed On Quaternary Zrnbtial Alloysmentioning
confidence: 99%
“…Using Raman spectroscopy, Gomez Sanchez et al [59] and Farina et al [15] found that the oxide film formed spontaneously on Zr in the air mainly has a tetragonal structure of ZrO2, whereas the oxide films formed on Zr and Zr-2.5Nb alloy by anodization present mainly a monoclinic structure of ZrO2. In the case of the anodized samples from Zr and Zr-2.5Nb alloy, the ZrO2 monoclinic film incorporated a new phase identified as a Zr phosphate demonstrating the incorporation of phosphate ions from the electrolyte [15,58,59]. Although experimental data on the crystallography of passive films on Zr-based materials are scarce, from these few antecedents it can be argued that the crystallographic structure of such oxide films depends strongly on the oxidizing medium employed.…”
Section: Comments On the Corrosion Resistance Of Passive Layers Formed On Quaternary Zrnbtial Alloysmentioning
confidence: 99%
See 1 more Smart Citation